The illimitable freedom of the human mind : Thomas Jefferson's idea of a university - O'Shaughnessy, Andrew Jackson (mrj / YBP CIP upgrade, 2021)
"The Illimitable Freedom of the Human Mind: Thomas Jefferson's Idea of a University is an accounting of Jefferson creating the University of Virginia. Using a biographical approach, this book shows that his vision did much to anticipate the modern university and that it was influential in the development of American higher education. Furthermore, the university distinguishes Jefferson as an advocate of a public education system"--